Amine-catalyzed cascade reactions of ketoses with 1, 3-dicarbonyl compounds1. Issue 56 (19th June 2015) - Richter, Celin; Voigt, Benjamin; Mahrwald, Rainer
<x xml:space="preserve">Abstract</x> An amine-catalyzed cascade reaction of ketoses with 1, 3-dicarbonyl compounds is described.